ChemInform Abstract: Four‐Component Reaction Leading to Highly Functionalized Sulfoalkoxy Carbonyl Compounds. Issue 29 (July 2015) - Sohail, Muhammad; Zhang, Yixin; Sun, Guangwei; Guo, Xin; Liu, Wujun; Liu, Chang; Zhao, Zongbao K.
Abstract A facile regio‐ and diastereoselective four‐component reaction of α, β‐unsaturated carbonyl compounds, a cyclic ether, a sulfonic acid, and a halogen reagent is developed under mild conditions to access α‐bromo‐β‐sulfoalkoxyl carbonyl derivatives with excellent trans‐selectivity.